Studi Fenomenologi Budaya Keselamatan Pasien Dari Perspektif Kepala Ruang Instalasi Rawat Inap di RSUD Raden Mattaher Jambi - Afridawati MJ; Meri Neherta; Fitra Yeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Patient safety culture is the key to support the achievement of improvement in the safety of the patient's head of the room as the operational manager responsible for delivering quality services to manage all the resources in Care unit, especially in the management of patient safety. Research aims to delve deeply into the safety of cultural patients from a room head perspective. Design research is a method of descriptive phenomenology, data collection with interviews Postamand field records. Participants in this study were taken with purposive sampling techniques with seven participants. Data analysis using Collaizi method. The results of this study identified seven themes, namely (1) Experience the culture of patient safety, (2) Dimension of patient safety culture, (based on results obtained by the head of the room need to understand the function of management in safety management Patients and improve supervision.